THE EFFECT OF TOTAL ASSET TURNOVER AND INVENTORY TURNOVER ON COMPANY VALUE - Vellicia Dwi Dafika; Muhammad Fauzan (Indragiri Research Center (ingreat), 2023)
This study aims to examine the effect of total asset turnover and inventory turnover on company value (case study on pharmaceutical sub-sector manufacturing companies listed on the IDX for the 2018-2022 period). The population in this study uses the purposive sampling method in pharmaceutical companies listed on the Indonesia Stock Exchange and based on the criteria that have been determined, a sample of 55 pharmaceutical companies is obtained. The analysis of research data is a quantitative analysis, a calculation tool using SPSS (Statistical Package Social Science) analysis. The value of the determination coefficient (R2) of 0.232 shows that the variables of total asset turnover and inventory turnover affect the company's value by 26% and the remaining 74% are influenced by other variables. The results of the total asset turnover test partially did not have a significant effect on the company's value. The test results on the inventory turnover variable partially did not have a significant effect on the company's value. The results of testing the variables of total asset turnover and inventory turnover simultaneously affect the value of companies in pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange. Based on the results of the research, companies should pay more attention to the efficiency of total asset turnover and inventory turnover in order to generate profits. For investors, you should pay more attention to the value of the company because the higher the stock price, the higher the stock market price.